Deciphering the origin and therapeutic targets of cancer of unknown primary: a case report that illustrates the power of integrative whole-exome and transcriptome sequencing analysis - Al Assaad, Majd; Shin, Nara; Sigouros, Michael; Manohar, Jyothi; Antysheva, Zoia; Kotlov, Nikita; Kiriy, Daria; Nikitina, Anastasiia; Kleimenov, Mikhail; Tsareva, Anastasiya; Makarova, Anastasiya; Fomchenkova, Victoria; et al. (Frontiers in Oncology, 2024)
Cancer of unknown primary (CUP) represents a significant diagnostic and therapeutic challenge, being the third to fourth leading cause of cancer death, despite advances in diagnostic tools. This article presents a successful approach using a novel genomic analysis in the evaluation and treatment of a CUP patient, leveraging Whole Exome Sequencing (WES) and RNA sequencing (RNAseq). The patient, with a history of multiple primary tumors including urothelial cancer, exhibited a history of rapid progression on empirical chemotherapy. The application of our approach identified a molecular target, characterized the tumor expression profile, the tumor microenvironment, and analyzed the origin of the tumor, leading to a tailored treatment. This resulted in substantial radiological response across all metastatic sites and the predicted primary site of the tumor. We argue that a comprehensive genomic and molecular profiling approach, like the BostonGene© Tumor Portrait, can provide a more definitive, personalized treatment strategy, overcoming the limitations of current predictive assays. This approach offers a potential solution to an unmet clinical need for a standardized approach in identifying the tumor origin for effective management of CUP.